Innate and Adaptive Immune Memory: an Evolutionary Continuum in the Host's Response to Pathogens - Netea, Mihai G; Schlitzer, Andreas; Placek, Katarzyna; Joosten, Leo A B; Schultze, Joachim L (Cell host & microbe, 2019)
Immunological memory is an important evolutionary trait that improves host survival upon reinfection. Memory is a characteristic recognized within both the innate and adaptive arms of the immune system. Although the mechanisms and properties through which innate and adaptive immune memory are induced are distinct, they collude to improve host defense to pathogens. Here, we propose that innate immune memory, or "trained immunity," is a primitive form of adaptation in host defense, resulting from chromatin structure rearrangement, which provides an increased but non-specific response to reinfection. In contrast, adaptive immune memory is more advanced, with increased magnitude of response mediated through epigenetic changes, as well as specificity mediated by gene recombination. An integrative model of immune memory is important for broad understanding of host defense, and for identifying the most effective approaches to modulate it for the benefit of patients with infections and immune-mediated diseases.